(untitled) (Journal of Academic Research, 2021)
Ranula is a term used to describe a soft, clear or bluish swelling that usually appear in the floor of mouth under the tongue. Ranulas are classified as simple, or plunging. Simple ranula occurs in the floor of the mouth as bluish coloured swelling while plunging ranula extends deeply into the submandibular and neck spaces to manifest clinically as a cervical swelling after herniation of the pseudocyst through the mylohyoid muscle. The present case reported a 5- year-old female patient with oral ranula. The classical clinical features of oral ranula as well as the surgical management of the case has been described in details. The case report also presents a comprehensive discussion of the recent literature on the oral ranula.